Test and theoretical investigation of an improved CFRP-steel tube composite member under axial compressive loading. (1st January 2022) - Liu, Zhuo-qun; Luo, Bin; Wang, Qiang; Qin, Yong-fang; Zhang, Wen-tong
Highlights: According to the test results, the winding direction and the number of CFRP layers have a great influence on the overall buckling load of the CFRP-STCM, and the longitudinal fiber reinforcement effect of each CFRP layer is about 12.10%, while the circumferential fiber and 45° fiber is less than 5%. The failure modes of the composite members are also closely related to the fiber direction of the composite member after overall buckling occurs. Among them, fiber breaking occurs in the members reinforced with longitudinal fibers, matrix cracking occurs in the specimens reinforced with circumferential fibers, and torsion occurs in the specimens reinforced with 45° fibers. The results of parametric finite element analysis show that the thickness of the adhesive layer, the number of CFRP layers, the diameter-thickness ratio of the steel pipe, and the initial defect value all have a great influence on the overall buckling capacity of the composite member. The above factors should be considered in the calculation of the load-bearing capacity. Based on the modified Perry-Robertson formula, the theoretical calculation method can reasonably predict the overall buckling bearing capacity of the axial compression composite member, which is convenient for engineering application. Compared with the experimental results, the maximum deviation of the proposed theoretical formula is 10.7%, the average value is −3.21%, and the coefficient of variation is −0.015. Abstract: This paper presents an experimental and numerical study on the mechanical characteristics of an improved CFRP steel tube composite members (CFRP-STCMs) under axial compressive loading. The CFRP-STCM was reinforced with a thick-walled steel tube at both ends to prevent local buckling of CFRP retrofitted equal thickness circular steel tube under axial compressive load. The main focus of the lab test was the effects of fiber winding directions and the test results reveal that the related specimen mainly suffers from overall buckling failure modes. The remaining failure characteristics of the test specimens vary with the change in the fiber winding direction. The longitudinal fiber winding direction has the most obvious reinforcement effect on the load-bearing capacity of the composite member. The ±45° fiber winding direction leads to obvious torsion failure modes after the overall buckling of the test specimen. The numerical modeling was carefully validated using the test results and an extensive parametric analysis was conducted covering a reasonably wide range of geometric configurations. Parameterized numerical analysis reveals that the initial geometric imperfections (initial curvature) and the geometric configurations of the composite member other than the thickness of the adhesive layer have a significant influence on the load-bearing capacity of the composite member. A modified theoretical method for predicting the critical load of the composite member is proposed based on the Perry-Robert stability formula. The proposed simplified formula can accurately predict the critical buckling load of CFRP-STCM with errors and coefficients of variation are −2.71% and −0.014, respectively.